EPIZOOTIC SITUATION REGARDING CATTLE MASTITISM IN THE CONDITIONS OF THE FARMS OF ASTARTA-KYIV FIRM - Nesteruk, V. S.; Nagorna, L. V. (Scientific Progress & Innovations, 2022)
Despite many years of development and improvement of treatment regimens for mastitis in cows, this pathology is still relevant in the conditions of livestock farms of various production facilities. The dynamics of mastitis is significantly influenced by the body's resistance, timeliness of diagnosis and further treatment. The aim of our work was to establish the prevalence of clinically severe forms of mastitis in cows kept in livestock farms of Poltava, Zhytomyr, Ternopil and Vinnytsia regions, which are part of the company "Astarta-Kyiv". To achieve this goal, the logs of reporting and accounting documentation of farms were analyzed; the percentage of cows incidence of clinical forms of mastitis in the comparative aspect with other nosological units registered in cows was studied; the dependence of the level of morbidity on the regional location of farms has been established. According to the results of research, during 2019–2021, the incidence of clinical forms of mastitis among cows at different stages of lactation averaged 25.92 %. The number of cows diagnosed with clinical forms of mastitis since 2019 has had a clear upward trend and amounted to 22.57 %, 25,82 % and 29.82 %, respectively, in 2019, 2020 and 2021. It was found that in the farms of the north-western regions (Zhytomyr, Ternopil and Vinnytsia regions) the frequency of clinical forms of mastitis in lactating cows was higher than in the farms of Poltava region and amounted to 30.66 %. In the following research years (2020–2021), the tendency to reduce the number of lactating animals in livestock farms in these regions persisted. There was also an excess of cases of diagnosis of clinical forms of mastitis in lactating animals. In the farms of the north-western regions during 2020–2021 these indicators amounted to 38.75 and 35.91 %, while in the farms of Poltava region they amounted to 18.51 and 24.54 %, respectively, for the same study period.